Preparation of biomineral filler and its application as biopolymer composite filler / Nur Damia Mohd Ismail - Nur Damia , Mohd Ismail (2013)
Lokan shell powder (LP), which is the source of biomineral Calcium Carbonate (CaCO3) has been incorporated into a biopolymer, PLA to produce thin film biocomposites. The incorporation of LP has been affecting the mechanical properties, crystallization and porosity of the PLA matrix. With the addition of LP , the stiffness of the composite was found to be increase significantly. In term of crystallization, the percentage of crystallinity decrease with the addition of LP and show significant drop at 8wt% filler content. FESEM result clearly showed the decrease in size and number of pores when LP is added to PLA matrix.